The politics of social inclusion and labor representation : immigrants and trade unions in the European context - Connolly, Heather, 1978-; Marino, Stefania, 1977-; Martinez-Lucio, Miguel, 1960- (ILR Press, an imprint of Cornell University Press, 2019)
"Compares trade union responses to immigration in the European context, specifically the Netherlands, Spain, and the United Kingdom"--